(untitled) (American Journal of Islam and Society, 1996)
The catch phrase "new world order" has shaped the view of the future differently for various groups and people. It has been associated mostly with former American president George Bush, who witnessed the end of the old system with the collapse of the Soviet Union and, with others, realized the beginning of a new order. Prior to the end of the cold war, Third World countries were calling for "new economic and political orders." Speaking before the General Assembly of the United Nations, Fidel Castro called for the establishment of a "new world order based on justice, on equity, on peace." And an altogether different new world order has been anticipated in the near future by such evangelists as Pat Robertson in his book The New World Order. Robertson believes the new order will commence with the rerurn of the Messiah, who will erect a new and just world. However, for prominent scholar Noam Chomsky, the new world order is merely a continuation of the old one. From the basis of three lectures delivered at the American University in Cairo in May 1993, Chomsky wrote World Orders, Old and New. The book is divided into three parts. The first part discusses the cold war and how it was used by the superpowers to justify all foreign and domestic political, economic, and military actions. “The Cold War provided easy formdas to justify criminal actions abroad and entrenchment of privileges at home.” Both sides were able to claim that such atrocities were committed to promote the “national security which was threatened by the other side.” ...